Validity of The Abtract Algebra Teaching Book - Sindi Amelia; Leo Adhar Effendi (Mathematics Research and Education Journal, 2020)
The Abstract Algebra is one of the most difficult subjects for students. In this course, students are required to have several textbooks as their reading source. However, the existing textbooks do not guide students in carrying out the process of preparing evidence and tend to speak non-Indonesian languages. The purpose of this research is to design and develop textbooks on abstract algebra courses which contain proofs in full step by step that can improve the ability to organize evidence. This type of research is development research with formative evaluation design consisting of self-evaluation, prototyping (expert reviews, one-to-one, and small groups), and field tests. The validity of the development of abstract algebra textbook is passed through the stages of self-evaluation and expert reviews. The results showed that the prototype of abstract algebra teaching books had a very high level of validity (89.29%).